1986
DOI: 10.1002/em.2860080607
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mouse liver stored vitamin A on the induction of mutations (Ames tests) and SCE of bone marrow cells by aflatoxin B1, benzo(a)pyrene, or cyclophosphamide

Abstract: Male mice (C57BL/6J) at 2 weeks of age were divided into two groups and maintained on a vitamin A-deficient or vitamin A-(retinyl acetate) supplemented diet. After 8 weeks, the average liver vitamin A concentration of mice fed on vitamin A-deficient or -supplemented diet was 36 +/- 7 micrograms/g vs 287 +/- 22 micrograms/g, respectively. Uninduced liver S9 fractions were prepared from both groups of mice and used to activate (with cofactors) the precarcinogens aflatoxin B1 (AFB), cyclophosphamide (CPP), dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…No such protective effect was observed in a preliminary experiment with benzo(a)pyrene (5 and 10 ~tg/dish), which is consistent with previous data [11]. The positive effect of BC in experiments with CP [1] (which requires an inductor of the microsomal enzyme system common to 2-acetylaminofluorene) implies its relationship with retinol [6] with respect to inhibitory effects against mutagens activated by certain forms of cytochrome P-450. Not one modification of the Ames test revealed an effect of BC on the mutagenicity of the three direct mutagens, which is in conformity with previous data [1,9].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…No such protective effect was observed in a preliminary experiment with benzo(a)pyrene (5 and 10 ~tg/dish), which is consistent with previous data [11]. The positive effect of BC in experiments with CP [1] (which requires an inductor of the microsomal enzyme system common to 2-acetylaminofluorene) implies its relationship with retinol [6] with respect to inhibitory effects against mutagens activated by certain forms of cytochrome P-450. Not one modification of the Ames test revealed an effect of BC on the mutagenicity of the three direct mutagens, which is in conformity with previous data [1,9].…”
Section: Resultssupporting
confidence: 90%
“…The specificity of the effect of BC was found in cultured CHO cells: when added to the culture medium, it reliably lowered the level of CA induced by directly acting mutagens but was inactive against others [10]. Since little has been reported on the antimutagenic effect of BC, established [1,6,9] and not established [1,9,11] in the Ames test, it seemed important to study this effect using modeled gene mutations in microbial cells.…”
mentioning
confidence: 99%
“…Further studies have to show whether the antimutagenic activity of myrcene is also relevant for the in vivo situation. For vitamin A and dietary carrot it could be demonstrated that an antimutagenic effect also exists in vivo [Qin and Huang, 1986;Darroudi et al, 19881. However, administration of P-myrcene to rats did not result in any significant effect on the hepatic drug metabolizing enzymes and in particular no significant change in the amount of PB-P-450 was found [Madyastha and Srivatsan, 1987;Austin et al, 19881.…”
Section: Discussionmentioning
confidence: 99%
“…The effects were determined in strains TA98 and TA100, where the authors considered that the observed capacity of the vitamin could be related with the inhibition of AFB1 metabolism or with an increased breakdown of the active metabolite (Busk & Ahlborg, 1980;Raina & Gurtoo, 1985). Other strains (TA102 and TA1535) were also tested and revealed positive results (Qin & Huang, 1986). In Chinese hamster V79 cells, (Huang et al, 1982) found a similar effect.…”
Section: Vitaminsmentioning
confidence: 99%